The Inefficiency of the Adjustment Mechanism in the Contemporary Global Economy. The Case of the United States and China - Janicka, Małgorzata (Comparative Economic Research. Central and Eastern Europe, 2022)
In the current international monetary system, the adjustment mechanism does not work properly to eliminate the excessive surpluses/deficits on the current accounts of the major countries that participate in international trade. Consequently, the adjustment changes do not take place in an evolutionary way, through market changes or decisions taken by the national authorities. They are the result of crises that reflect the unfavourable macroeconomic situation in different countries. The article explains the functioning of the adjustment mechanism in the contemporary international monetary system and the circumstances in which significant imbalances emerge at the global (US–China) level. Increasing external imbalances are an immanent systemic feature of the contemporary international monetary system. The lack of an adjustment mechanism in this system leads to the potentially cyclical emergence of such imbalances and their correction by crises. Thus, the current post‑crisis period may only be a stage before the next period of growing imbalances. The remedy for this threat lies in correcting the existing principles of the system.